The role of national culture as a lens for stakeholder evaluation of corporate social performance and its effect on corporate reputation - Clara Pérez-Cornejo; Esther de Quevedo Puente; Juan-Bautista Delgado-García (BRQ Business Research Quarterly, 2023)
Studies have shown that corporate social performance (CSP) is an antecedent of corporate reputation, acting as a signal that affects stakeholders' perceptions and expectations about a firm's future behavior. However, the perceptions, expectations, and interests of stakeholders may be affected by external factors, such as national culture, which shapes their beliefs about what role companies play in society. Drawing on institutional theory and Hofstede's cultural dimensions, we analyze how stakeholders' national culture moderates the relationship between CSP and corporate reputation. The results of the analysis of an international sample for the period 2010 to 2016 show that low individualism (i.e., collectivism), low masculinity (i.e., femininity), low power distance, and low uncertainty avoidance intensify the positive relationship between CSP and corporate reputation.
Keywords: M14; L14; 650; Corporate reputation; corporate social performance; stakeholder approach; national culture